The effects of electron irradiation and fluoride salt melt ZrF₄ – NaF on mechanical properties of Hastelloy N type alloys - Azhazha, V.M.; Bakai, A.S.; Dovbnya, A.N.; Коvtun, К.V.; Lavrinenko, S.D.; Malykhin, D.G.; Pylypenko, M.M.; Savchenko, V.I.; Semenov, N.A.; Strygunovsky, S.V.; Shramenko, B.I.; Wanderka, N. (Вопросы атомной науки и техники, 2005)
NSC KIPT has cast Hastelloy N type alloys that are to be used in molten-salt reactors (MSR). A study was made on the collective effects of exposure to electron irradiation and melt of sodium and zirconium fluorides at the temperature 650°С for 700 hours on mechanical properties of those alloys.